Increasing Consumer Loyalty Based On Product Quality In The Emina Brand: - - Syaharany, Lailla; Triastuti, Desy; Dyah Kusumastuti, Anggit (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
In this era of globalization and industry, many similar companies have sprung up in the field of cosmetics, causing increasingly fierce competition. So that to maintain consumer loyalty it is necessary to maintain product quality. This study's goal was to ascertain of increasing consumer loyalty based on product quality in the Emina brand. This research approach employs qualitative techniques and literature reviews that are drawn from pertinent earlier theories and publications. The findings indicate that the strategy to increase consumer loyalty based on product quality in the Emina brand by maintaining the ingredients used because it has obtained a halal certificate by LPPOM MUI. Keywords : Product Quality, Consumer Loyalty, Emina Products